Blocking VCAM-1 inhibits pancreatic tumour progression and cancer-associated thrombosis/thromboembolism. Issue 9 (21st October 2020) - Sano, Makoto; Takahashi, Ryota; Ijichi, Hideaki; Ishigaki, Kazunaga; Yamada, Tomoharu; Miyabayashi, Koji; Kimura, Gen; Mizuno, Suguru; Kato, Hiroyuki; Fujiwara, Hiroaki; Nakatsuka, Takuma; Tanaka, Yasuo; et al.
Abstract : Objective: Pancreatic ductal adenocarcinoma (PDAC) is the deadliest cancer. Cancer-associated thrombosis/thromboembolism (CAT), frequently observed in PDAC, is known as a poor prognostic factor. Here, we investigated the underlying mechanisms between PDAC and CAT, and performed a trial of therapeutic approach for PDAC using a genetically engineered mouse model, PKF ( Ptf1a cre/+ ;LSL-Kras G12D/+ ;Tgfbr2 flox/flox ). Design: Presence of CAT in PKF mice was detected by systemic autopsy. Plasma cytokines were screened by cytokine antibody array. Murine and human plasma atrial natriuretic peptide (ANP) and soluble vascular cell adhesion molecule 1 (sVCAM-1) were determined by ELISA. Distribution of VCAM-1 in PKF mice and human autopsy samples was detected by immunohistochemistry. PKF mice were treated with anti-VCAM-1 antibody and the effects on survival, distribution of CAT and the tumour histology were analysed. Results: We found spontaneous CAT with cardiomegaly in 68.4% PKF mice. Increase of plasma ANP and sVCAM-1 was observed in PKF mice and PDAC patients with CAT. VCAM-1 was detected in the activated endothelium and thrombi. Administration of anti-VCAM-1 antibody to PKF mice inhibited tumour growth, neutrophil/macrophage infiltration, tumour angiogenesis and progression of CAT; moreover, it dramatically extended survival (from 61 to 253 days, p<0.01). Conclusion: Blocking VCAM-1/sVCAM-1 might be a potent therapeutic approach for PDAC as well as CAT, which can contribute to the prognosis. Increase of plasma ANP and sVCAM-1 might be a diagnostic approach for CAT in PDAC.